Kontribusi Usaha Mikro, Kecil, dan Menengah (UMKM) di Sektor Pariwisata terhadap Pertumbuhan Ekonomi di Desa Aik Berik - Mayani Kusuma; Sanwani Sanwani; Refreandi Haeri (Tirai Edukasi : Jurnal Pendidikan, 2026)
This study aims to analyze the contribution of Micro, Small, and Medium Enterprises (MSMEs) in the tourism sector to economic growth in Aik Berik Village, Central Lombok Regency. Using a qualitative case study design, data were collected through observation, interviews, and documentation. The results indicate that tourism MSMEs in Aik Berik, such as homestays, culinary businesses, handicrafts, and tour guide services, play a crucial role in increasing community income, creating jobs, and strengthening the local economy. However, MSMEs still face challenges such as limited access to capital, inadequate infrastructure, and a lack of digital marketing skills. These findings highlight the need for government policy support and stakeholder collaboration to strengthen tourism MSMEs towards sustainability and inclusivity.